Regulatory Fragmentation of Tourism within Regional Autonomy and Its Implications for the Challenges of Destination Management by Local Governments - Muhammad Mas Davit Herman Rudiyansah; Sucipto Sucipto (Jurnal Pariwisata Nusantara (JUWITA), 2025)
Purpose: This study aims to analyze the issue of regulatory fragmentation in the management of tourist destinations by local governments within the framework of regional autonomy in Indonesia through a normative juridical analysis. The main focus lies on the disharmony of the relationship between the central and regional governments that impacts the effectiveness of tourist destination governance, with a case study of the management of the Borobudur Temple Area. Method: Using a normative approach, this study examines legal provisions such as Law No. 10 of 2009 concerning Tourism and Law No. 23 of 2014 concerning Regional Government, as well as other implementing regulations and non-statutory legal documents. Analysis is conducted on the interaction and overlap between regulations, as well as their impact on the implementation of authority in the field. Result: The results of the study indicate that although regional autonomy is regulated normatively, the practice of managing tourist destinations is still dominated by the central government, which tends to ignore the strategic role of the regions. This dominance not only weakens the capacity of regional decision-making but also creates inequality in the distribution of economic benefits, legal uncertainty for business actors, and social resistance from local communities. This study highlights the need for regulatory harmonization between the central and regional governments through a collaborative approach, strengthening regional institutional capacity, and actively involving local communities in policy formulation and implementation. Contribution: A key contribution of this research is the proposed tourism destination governance model based on the principles of distributive justice, intergovernmental synergy, and public participation. By integrating constitutional law and public administration perspectives, this study emphasizes that decentralization must be implemented substantively, not merely as a formality. Strengthening a responsive, inclusive, and contextual regulatory framework is a key prerequisite for realizing a sustainable, equitable tourism sector capable of significantly improving the welfare of local communities.